Simple and Rapid HPLC Separation and Quantification of Flavonoid, Flavonolignans, and 2,3-Dehydroflavonolignans in Silymarin - Petrásková, Lucie; Káňová, Kristýna; Biedermann, David; Křen, Vladimír; Valentová, Kateřina (Foods (Basel, Switzerland), 2020)
Herbal preparations from Silybum marianum have been used since the fourth century BC in liver disease treatment and against numerous other pathologies. Consumption of silymarin containing drugs and food supplements continues to increase. Precise, fast, reliable, and complex determination of all components of silymarin preparations is paramount for assessing its pharmacological quality. We present here simple and fast HPLC-DAD and LC-MS analytical methods for the determination and quantification of all known silymarin components, including 2,3-dehydroflavonolignans that has not been achieved so far. The first method, using a common C18 column, allows baseline separation of previously inseparable silychristin A, B, isosilychristin, and silydianin. Moreover, this method allowed detection of three so far unknown silymarin components. In addition, the first analytical separation of enantiomers of 2,3-dehydrosilybin was achieved using a Lux 3μ Cellulose-4 chiral column, providing even more accurate description of silymarin composition. 2,3-Dehydroflavonolignans were isolated for the first time from silymarin using preparative chromatography on C18 and ASAHIPAK columns, and 2,3-dehydrosilychristin and 2,3-dehydrosilybin were for the first time conclusively confirmed by HPLC, MS, and NMR to be silymarin components. Using the optimized analytical methods, six various silymarin preparations were analyzed showing substantial differences in the composition.
Keywords: flavonolignans; enantiomers; quantification; silymarin; diastereoisomers; HPLC-MS separation; milk thistle